Modeling of indicators of the chemical industry enterprises’ strategy - O. Chernysheva (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2022)
The article is devoted to the formation of a mathematical model of the volume of production of competitive products as one of the main indicators that determines the strategy of the chemical industry enterprises to ensure their sustainable development. It is noted that the volume of production determines the enterprise's share in the competitive market, on the one hand, and the level of resource use - on the other. In the chemical industry, the volume of production (sales) and profitability of activities in the sectors of the industry are indicators that used to characterize the strategy. It is offered to study the influence of factors on production volumes using multifactor linear correlation-regression models, and to form the composition of factors according to their impact on the competitiveness of products in strategic areas of management of the chemical industry enterprises. The components of the mathematical model for determining the production volumes of chemical industry enterprises (target function and system of restrictions) are proposed to be formed on the basis of multifactor models of influence on production volumes in strategic areas of management taking into account the risks that exist in production and sales. On the basis of the developed mathematical model it is offered to solve a task of definition of optimum volumes of manufacture of competitive products of the chemical industry enterprise for each assortment unit in strategic areas of management by a method of linear programming. Taking into account the influence on the competitiveness of products in tire production, multiple correlation-regression models of volumes of production in groups of passenger, truck and agricultural tires, as well as a mathematical model of production volumes of competitive tire products have been built. Within this model, a set of management decisions to increase the competitiveness of products has been applied. It has been proved that the use of the built model in the competitiveness management system contributes to the increase the gross profit and providing sustainable development of the tire production enterprise.